2400 - Ang, Kai Lin (2018)
Sports has been commonly mistaken as to be associated for just health or survival benefits, and also as a form of distraction to most who prize practicality. Sports should rather, be tied closely to many domains of life that are beyond its commonly perceived value for sports itself, and to other life values. In fact, sports can be a means to cultivate values of respect, discipline and teamwork. If so argued, values development is also commonly associated with the competitive sporting arena, except that there lacks in study of values development through unorganized sports activities. The generally undermined benefits of sports further highlight the need for this study to showcase the importance of sports in character development, especially with the dwindling participation in sporting activities in Singapore. This design study seeks to explore and visualize how can unorganized sports activities be of benefit as a source of value creation to each Singaporean individual, by highlighting the potential importance of learning through sports by reflective observation, photo documentation of the activities of recreational sports in the Singapore landscape and interviews with the participants.